Co-administration of GnRH agonists with vaginal progesterone compared to vaginal progesterone in luteal phase support of the frozen-thawed embryo transfer cycle: An RCT - Afsoon Zareii; Sara Davoodi; Mahshid Alborzi; Marzieh Eslami Moghadam; Elham Askary (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Background: Since progesterone alone does not seem to be enough for luteal phase support (LPS), especially in frozen embryo transfer (FET) cycles, so gonadotropin-releasing hormone agonist (GnRH-a) is suggested as an adjuvant therapy in combination with progesterone for LPS. Objective: To evaluate the effects of the administration of GnRH-a with vaginal progesterone compared to vaginal progesterone alone in luteal phase support of the frozen-thawed embryo transfer cycles. Materials and Methods: In this randomized controlled clinical trial, 240 infertile women who were candidates for FET were evaluated into two groups (n = 120/each). Group I received 400 mg vaginal progesterone twice a day from the time of transfer. The second group received vaginal progesterone and also 0.1 mg diphereline on days 0, 3, and 6 of FET for LPS. Finally, the clinical and ongoing pregnancy rates, and the implantation, and spontaneous abortion rates were compared in two groups. Results: Results showed that there was no significant difference between the mean age of women and the duration of infertility (p = 0.78, p = 0.58, respectively). There were no significant differences between groups in the terms of implantation and spontaneous abortion rates (p = 0.19, p = 0.31, respectively). However, in terms of clinical and ongoing pregnancy rates, the significant differences were seen between groups (p = 0.008 and p = 0.005, respectively). Conclusion: Co-administration of GnRH-a and vaginal progesterone in LPS may be superior to vaginal progesterone alone in women who underwent a frozen-selected embryo transfer cycle.